Implikasi Sikap dan Perilaku Siswa Melalui Pendidikan Moderasi Beragama Dalam Penguatan Karakter Era Digitalisasi: Studi di Sekolah Dasar Perbatasan Indonesia-Malaysia - Putra, Purniadi; Arnadi; Hadisa Putri (JIP Jurnal Ilmiah PGMI, 2023)
The purpose of this research is to determine and analyze the formation of the character of tolerance through religious moderation education in the digital era at the Indonesia-Malaysia border elementary school. Religious moderation education is important as a means of strengthening the character of students at the border, who often experience complex social and cultural dynamics. In this research, a qualitative approach was used, and case studies were carried out at several schools in border areas. Data collection was carried out through observation, interviews conducted with the teacher of the Nurul Yaqin Islamic Elementary School of Sijang, the Headmaster, parents of students and students in fifth grade and analysis of documents related to the program created to build the character of tolerance in the Indonesia-Malaysia border area. The results of this research show that the value of tolerance is taught to students through the delivery of material in class. Apart from that, students are trained by directing them to be tolerant among each other, one of which is by respecting the opinions of fellow friends during discussion sessions, one of which is respecting different opinions as something natural. and human. Religious activities at Nurul Yaqin Islamic Elementary School of Sijang are carried out every Islamic holiday by holding various activities and competitions at the Madrasah. PHBI activities, starting from the Prophet's birthday, Isra' Mikraj, and the Hijriyah New Year, are a very effective means of grounding Islam.